Plasminogen Assay by Means of the Lysis Time Method - Berg, W; Korsan-Bengtsen, K; Ygge, J (Thrombosis and Haemostasis, 1965)
The lysis time method for the determination of plasminogen has been investigated using plasminogen-free thrombin and fibrinogen preparations.The experiments have shown that the lysis of a fibrin clot is the result of two consecutive reactions: the formation of fibrin which proceeds as a first order reaction and the degradation of fibrin which proceeds as a zero order reaction. Plasminogen is activated in a separate reaction. If the rate of the fibrin formation is much greater than the rate of degradation, the lysis of the fibrin clot is approximately of zero order in fibrin. The lysis time will then be inversely proportional to the plasmin concentration and proportional to the fibrinogen concentration. In a double logaritmic system the correlation between lysis time and plasmin activity is a straight line with a slope of 135°.Plasminogen is rapidly activated with streptokinase. Maximal activation is obtained only with a certain streptokinase concentration. Higher concentrations inactivate plasmin and with lower concentrations, the maximal activity is never reached. A spontaneous inactivation is seen after about 30 minutes. With urokinase, a higher maximal plasminogen activity is obtained than with streptokinase. Urokinase in higher concentrations does not inactivate plasmin.A standard assay for determination of plasminogen by the lysis time method has been worked out and is based on these results.